T@pped into the W3rldWideWeb: C0nfigur-ing [Net(I)Ana(S)] - Menéndez Cuesta, Vanesa (My University, 2021)
The purpose of this paper is to explore the ways in which loneliness has become the epitome of contemporary human condition for the Millennial generation, together with its impact on the psychological and emotional side of human expression and the urban landscape, as expressed through art and the virtual. Modern megacities are shaping and configuring what we nowadays understand as art. In the case of Alt [C]Lit poets, whether it is New York City or Los Angeles, the US urban landscape has a great influence on how these young authors have configured their poetic production: their experiences and referents belong to these cities. In this paper, I would like to discuss how spaces, especially urban spaces, have generated physical isolation and have transitioned into a mental landscape, to which the virtual contributes to increase anxious alienation that manifests itself through the body and the configuration of human subjectivities. Therefore, I will analyze hypermodern identity/ies that result from the urban landscape of megalopolises, the manner in which the virtual has generated online communities and has contributed to (hyper)sexualization, and the way in which Zafra¿s concept of netianas can be applied in order to analyze the paradoxical position of loneliness and early-adulthood through the Alt [C]Lit poetry and other related-literary and visual production. Keywords: overexposure, online identities, loneliness, non-places, visual culture, Alt [C]Lit poetry